NCN‐Coordinating Ligands based on Pyrene Structure with Potential Application in Organic Electronics. Issue 62 (18th October 2017) - Zych, Dawid; Kurpanik, Aneta; Slodek, Aneta; Maroń, Anna; Pająk, Michał; Szafraniec‐Gorol, Grażyna; Matussek, Marek; Krompiec, Stanisław; Schab‐Balcerzak, Ewa; Kotowicz, Sonia; Siwy, Mariola; Smolarek, Karolina; et al.
Abstract: Five novel derivatives of pyrene, substituted at positions 1, 3, 6, 8 with 4‐(2, 2‐dimethylpropyloxy)pyridine (P1 ), 4‐decyloxypyridine (P2 ), 4‐pentylpyridine (P3 ), 1‐decyl‐1, 2, 3‐triazole (P4 ), and 1‐benzyl‐1, 2, 3‐triazole (P5 ), are obtained through a Suzuki–Miyaura cross‐coupling reaction or Cu I ‐catalyzed 1, 3‐dipolar cycloaddition reaction, respectively, and characterized thoroughly. TGA measurements reveal the high thermal stability of the compounds. Pyrene derivativesP1 –P5 all show photoluminescence (PL) quantum yields (Φ) of approximately 75 % in solution. Solid‐state photo‐ and electroluminescence characteristics of selected compounds as organic light‐emitting diodes are tested. In the guest–host configuration, two matrixes, that is, poly( N ‐vinylcarbazole) (PVK) and a binary matrix consisting of PVK and 2‐tert‐butylphenyl‐5‐biphenyl‐1, 3, 4‐oxadiazole (PBD) (50:50 wt %), are applied. The diodes show red, green, or blue electroluminescence, depending on both the compound chemical structure and the actual device architecture. In addition, theoretical studies (DFT and TD‐DFT) provide a deeper understanding of the experimental results. Abstract : Pyrene derivative diodes : Novel 1, 3, 6, 8‐tetrasubstituted pyrene derivatives are developed, which show improved thermal stability and can act as efficient luminophores with high photoluminescence quantum yields (see figure). These compounds are promising for application in organic light‐emitting diodes.